Optimization of Museums as Learning Media Through the Melali Sambilang Melajah Program to Increase Students’ Interest in Learning History - Wijaya, Gede Arista (Jayapangus Press, 2026)
Character formation through history learning can be achieved when students understand the meaning and values embedded in historical events. History education contributes to the development of nationalism, patriotism, civic responsibility, democratic attitudes, humanitarian awareness, and cultural insight rooted in noble historical values. However, these objectives require increased student interest in learning history, which can be fostered through innovative learning programs and the effective use of educational media. This study aims to analyze the optimization of museums as learning media through the Melali Sambilang Melajah program to enhance students’ interest in learning history. The research employed a qualitative approach using literature review, observation, and interviews as data collection methods. The literature review examined books, academic journals, seminar proceedings, and related studies on museums, history learning, instructional media, historical sites, and student learning interest. Observations and interviews were conducted at the Bali Museum and the Balinese People’s Struggle Monument to examine their relevance to high school history learning. The findings indicate: (1) the strong relevance of the collections at the Bali Museum and the Balinese People’s Struggle Monument to history learning materials in senior high school; and (2) the implementation of the Melali Sambilang Melajah program effectively optimizes museums as educational media while increasing students’ interest in learning. Historical artifacts and dioramas provide concrete visual representations of past events, enabling students to contextualize historical narratives and emotionally engage with historical experiences. Consequently, museums and monuments function not only as heritage preservation institutions but also as effective educational media that enhance students’ learning interest.